Comparação da atividade de proliferação celular nos fibromas odontogênicos e ossificantes - Bruna Goncalves Garcia (2008)
Central (COF) and peripheral (POF) odontogenic fibroma are benign odontogenic tumours. Peripheral ossifying fibroma (PEOF) is a non neoplastic reactive lesion. Central ossifying fibroma (CEOF) is a benign neoplasm fibro-osseous lesion. The aim of this study was to evaluate comparatively the cellular proliferative activity in these lesions. Immunohistochemistry to PCNA and the AgNOR protocol were performed in POF (9 cases), COF (4 cases), PEOF (8 cases) and CEOF (7 cases) belonging to the Oral Pathology Service of the Sao Paulo and Minas Gerais Universities. Quantitative and morphometric analysis of AgNOR and PCNA index were determined. Statistical analysis was performed with significance at the 0.05 level. Central lesions presented higher AgNOR number and PCNA index than peripheral lesions in the mesenchymal component (p=0,05). AgNOR number in the epithelial component was higher in the central odontogenic fibroma than in the peripheral odontogenic fibroma (p=0,05). Mesenchymal and epithelial components presented similar AgNOR number and PCNA index in the central odontogenic fibroma and similar AgNOR number in the peripheral odontogenic fibroma (p=0,05). All the four types of lesions showed a profile of a benign neoplasm (COF and CEOF) or of a non neoplastic reactive lesion (POF and PEOF). These findings reflect that the POF may represent a non neoplasm reactive lesion in the resemblance of the PEOF. Also, the epithelial and the mesenchymal components of POF and COF showed similar cellular proliferative activity.